Reconstructed precipitation on a centennial timescale from tree rings in the western Tien Shan Mountains, Central Asia. (9th February 2015) - Zhang, Tongwen; Zhang, Ruibo; Yuan, Yujiang; Gao, Yaqi; Wei, Wenshou; Diushen, Mamatkanov; He, Qing; Shang, Huaming; Wang, Jia
Abstract: July–June precipitation has been reconstructed to 1756 AD for the western Tien Shan Mountains, Central Asia, using the Picea schrenkiana tree-ring width. The reconstruction explains 31% of the variation in the observed precipitation from 1933 to 2009. Some extremely dry signals in the historical documents are captured precisely in this new reconstruction. Wet periods occurred during the periods of 1811–1828, 1843–1880, 1893–1915, 1929–1934, and 1983–2002, while the periods 1766–1810, 1829–1842, 1881–1892, 1916–1928, and 1935–1982 were relatively dry. Power spectral and wavelet analyses demonstrated the existence of significant 32-, 17-, and 2.6–7.4-year cycles of variability. An assessment of spatial correlation analysis and the significant correlation coefficients between the reconstructed precipitation series and three precipitation reconstructions indicate that our reconstruction might contain multiple large-scale climatic signals in the low-frequency domain. A wetting trend in the eastern Central Asia since the 1970s decades was also captured by this reconstruction.